An inorganic geochemical argument for coupled anaerobic oxidation of methane and iron reduction in marine sediments. Issue 2 (27th January 2014) - Riedinger, N.; Formolo, M. J.; Lyons, T. W.; Henkel, S.; Beck, A.; Kasten, S.
Abstract Here, we present results from sediments collected in the Argentine Basin, a non‐steady state depositional marine system characterized by abundant oxidized iron within methane‐rich layers due to sediment reworking followed by rapid deposition. Our comprehensive inorganic data set shows that iron reduction in these sulfate and sulfide‐depleted sediments is best explained by a microbially mediated process—implicating anaerobic oxidation of methane coupled to iron reduction (Fe‐AOM) as the most likely major mechanism. Although important in many modern marine environments, iron‐driven AOM may not consume similar amounts of methane compared with sulfate‐dependent AOM. Nevertheless, it may have broad impact on the deep biosphere and dominate both iron and methane cycling in sulfate‐lean marine settings. Fe‐AOM might have been particularly relevant in the Archean ocean, >2.5 billion years ago, known for its production and accumulation of iron oxides (in iron formations) in a biosphere likely replete with methane but low in sulfate. Methane at that time was a critical greenhouse gas capable of sustaining a habitable climate under relatively low solar luminosity, and relationships to iron cycling may have impacted if not dominated methane loss from the biosphere.